A Conceptual Development of Risk and Well-Being in Homestay Tourism: Facing the Post Covid-19 Era - Ardianto, Eka; Sugiarto, Sugiarto (Journal of Business on Hospitality and Tourism, 2022)
Entering the “New Era” tourists could “recharge” their well-being yet tourists also still facing varieties of risks due to more than two years the tourism destination have no visitors therefore, for instance, control and maintenance in their facilities are questionable. The aim of this study is to analyses a conceptual development of Risk and Well-Being to manage tourists to revisit in homestay tourism facing the Post Covid-19 era. This study is using review literatures of Homestay’s Risk Classification; Service Quality; Well-Being; Subjective Well-Being (SWB) on Tourism; Risk Management and SWB; and Risk Management, SWB, and Tourism, then examine a conceptual development. The conceptual development of Risk and Well-Being consists of model and matrix of Risk and Well-Being.  The study proposes six proposition: P1: SERVQUAL influences Risk Management; P2: Risk Management serves as a contributor to Eudaimonic well-being; P3: Risk Management serves as a contributor to Hedonic well-being; P4: Eudaimonic well-being leads to Intention to Revisit; P5: Hedonic well-being leads to Intention to Revisit; P6: There are 2 dimensions of Risk and Well-Being Matrix that consists of: reflexivity; reactivity; reconnectability; and recreativity.